Tracking the Implementation of Hybrid Contract Transactions in Islamic Banking Products in Indonesia - Rani Mariana; Mohamad Anton Athoillah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Islamic Banking Product Development Is Believed To Be One Of The Parameters Of The Ability Of Islamic Banks To Adapt To Modern Human Needs. Basically, Islamic Banks Have Made Several Innovation Efforts, One Of Which Is By Engineering Contracts In Fiqh Muamalah. Some Contracts In Fiqh Muamalah Are Not Only Adopted, But Also Adapted By Islamic Banks So That They Are In Accordance With The Needs Of The Community. The Principle Of Freedom In Islam Is The Main Capital In Facing The Complexity Of Economic Problems And The High Needs Of The Community For The Role Of Islamic Banks. Hybrid Contract (Al-'Uqud Al-Murakkabah) Is One Example Of An Islamic Bank Strategy In Developing Business Innovation. Hybrid Contract Is An Agreement Between Two Parties To Do Business That Includes Two Or More Contracts. Hybrid Contracts Have Been Used In Various Islamic Bank Products. For Example, IMBT, Property Financing, Sharia Card, Takeover Financing, Sharia Pawn, Current Account Products, Sharia Current Account Financing, Sharia Bonds, And Sharia Hedging.